Meltdowns and media: Moment-to-moment fluctuations in young children's media use transitions and the role of children's mood states. (November 2022) - Coyne, Sarah M.; Rogers, Adam; Shawcroft, Jane; Reschke, Peter; Barr, Rachel; Davis, Emilie J.; Holmgren, Hailey G.; Domoff, Sarah
Abstract: Recent research has started to examine problematic media use in early childhood. However, the vast majority of research has been questionnaire based, has assumed relative within-person stability in problematic media use patterns, and has rarely examined antecedents to problematic media use. We utilized an ecological momentary assessment design (EMA) in the current study to tease apart within- and between-subjects variability in media use and examine how one antecedent, child mood, was related to positive and negative transitions away from media. Two-hundred forty-three parent-child dyads ( M child age = 41.17 months, SD = 3.06 months) took part in an EMA assessment of media use multiple times each day over seven days. Parents reported on (1) their child's mood prior to the media use (energetic, happy, bored, upset), (2) their reason for having the child use media in that instance, and (3) the child's behavior as they transitioned away from media. Findings indicated that child energetic mood prior to media use was associated with a better transition away from media. Additionally, a majority of variability resided at the within-person level and was not explained by normal fluctuations in the day of the week (weekday vs. weekend). Children were also less likely to transition well if parents used media to regulate their child's negative emotion. Implications for parents are discussed. Highlights: There is a large amount of variability in children's problematic transitions around media during early childhood. When children are energetic before media use, they tend to transition better away from media. When parents use media as a way to calm children down, children are less likely to transition well to the next activity. Ecological momentary assessment is a unique method to capture problematic media use during early childhood.